Learning the Language of Locomotion: Do Children Use Biomechanical Structure to Constrain Hypotheses about Word Meaning?. Issue 4 (1st October 2016) - Malt, Barbara C.; White, Anne; Ameel, Eef; Storms, Gert
ABSTRACT: Much has been said about children's strategies for mapping elements of meaning to words in toddlerhood. However, children continue to refine word meanings and patterns of word use into middle childhood and beyond, even for common words appearing in early vocabulary. We address where children past toddlerhood diverge from adults and where they more closely approximate them, and why. In two studies, we examined naming of locomotion (walking, running, hopping, etc.) by children aged four to nine and compared their patterns of word use to adult patterns. We evaluated whether the children are sensitive to the biomechanical discontinuity between pendulum-type and impact-and-recoil-type actions that constrains adult word use. We also evaluated whether they appreciate this constraint by age four or only develop appreciation later. Children from four onward were sensitive to the biomechanical distinction in their word use. Perceived domain structure plays a role in explaining later lexical development.